Quantifying extreme climatic conditions for maize production using RZWQM in Siping, Northeast China - Liu, Haijun; Liu, Yu; Zhang, Liwei; Zhang, Zhijun; Gao, Zhuangzhuang (International Journal of Agricultural and Biological Engineering, 2019)
Climate change has a great influence on agricultural production, especially under extreme climatic conditions. In this study, Root Zone Water Quality Model (RZWQM) was used to predict grain yields of maize in the Siping region, Jilin Province, Northeast China during the period from 1951 to 2015; and the response of grain yield to main climatic variables was qualitatively analyzed, especially in three special years of 1954, 2000 and 2009. Results showed that 1°C increase for minimum, maximum and mean air temperatures may produce 1224 kg/hm2, 1860 kg/hm2 and 1540 kg/hm2 more grain yields, respectively, and seasonal rainfall amount of less than 450 mm, especially at the flowering and grain filling stages, greatly reduced grain yields. In the years of 1954, 2000 and 2009, grain yields were reduced by 41%, 47% and 40% compared to their mean value, respectively, correspondingly because of extra low temperature (lower by 2.1°C-2.3°C), less rainfall at the grain filling stage (36 mm) and extra high temperature (higher by 1.7°C-1.8°C), and less seasonal rainfall (252 mm). To reduce extreme climate’s effects on grain yield, it is suggested that supplementary irrigation at the flowering and grain filling stages should be provided when rainfall is much less at this stage and also appropriate maize species based on the longtime weather forecast should be selected. Keywords: climate change, RZWQM, extra low and high temperatures, seasonal rainfall distribution, maize yield response, Northeast China DOI: 10.25165/j.ijabe.20191202.3388 Citation: Liu H J, Liu Y, Zhang L W, Zhang Z J, Gao Z Z. Quantifying extreme climatic conditions for maize production using RZWQM in Siping, Northeast China. Int J Agric & Biol Eng, 2019; 12(2): 111–122.